AVALIAÇÃO DO PERFIL COMPORTAMENTAL SOBRE A REPRODUÇÃO DO LAMBARI (Astyanax sp.) - DALEGRAVE, Caroline de Brito; GONÇALVES, Isabela Pinto; FERREIRA, Igor de Oliveira; SILVA, Gabriel dos Santos; SANTOS, Emmanuel Jarsen dos; COSTA, Deliane Cristina (ANAIS DO ENIC, 2022)
-